Evaluation of the protective role of resveratrol on LPS-induced septic intestinal barrier function via TLR4/MyD88/NF-κB signaling pathways - Zhongliang Shi; Yanna Jiao; Zhizhen Lai; Juan Liu; Bo Yang; Mahong Hu; Jianbiao Meng (Scientific Reports)
Abstract The intestinal barrier function is a critical defense mechanism in the human body, serving as both the primary target and initiating organ in cases of sepsis. Preserving the integrity of this barrier is essential for preventing complications and diseases, including sepsis and mortality. Despite this importance, the impact of resveratrol on intestinal barrier function remains unclear. Thus, this study aims to explore the potential beneficial effects of resveratrol on maintaining intestinal barrier function. Fifteen male Sprague Dawley rats, weighing between 180 g and 220 g, were randomly assigned to one of three groups: the control group (Con), the lipopolysaccharide (LPS) group, and the resveratrol (RSV) group. The resveratrol group received an intravenous administration of resveratrol at a dosage of 8 mg/kg, 10 min prior to lipopolysaccharide treatment. Each group comprised five rats. Various techniques including enzyme-linked immunosorbent assay (ELISA), hematoxylin and eosin staining (HE), periodic acid Schiff (PAS) staining, transmission electron microscopy (TEM), Western blot analysis (WB), and quantitative real-time polymerase chain reaction (qRT-PCR) were utilized to assess differences in inflammatory cytokine expression, histopathological changes, apoptosis, tight junction (TJ) protein, and the TLR4/MyD88/NF-кB signaling pathways. Resveratrol exhibited anti-inflammatory effects by decreasing levels of interleukin (IL)-1β, interleukin(IL)-6, and tumor necrosis factor (TNF)-α, while increasing interleukin (IL)-10. Additionally, in rats treated with resveratrol, there was a reduction in the expression of apoptosis-associated proteins Bax and Caspase-3. Resveratrol also significantly increased the expression of intestinal tight junction proteins (TJ), and decreased the levels of intestinal fatty acid binding protein (I-FABP) and D-lactic acid (D-LA). Furthermore, the expression of proteins in the related signaling pathways TLR4, MyD88, and NF-κB was decreased. Resveratrol has been shown to reduce the expression of intestinal apoptotic proteins, enhance the expression of intestinal tight junction proteins, and inhibit the inflammatory response mediated by the TLR4/MyD88/NF-κB signaling pathway, thereby alleviating LPS-induced septic intestinal injury.